Negotiating through the Intervention of A Third Party: The Functions of the Mediation During Peaceful Negotiations - Latifi Veton (SEEU Review)
The paper explores the functions of mediation during peaceful negotiations with a focus on the roles and models of intervention by a Third Party. The paper aims particularly to identify the conditions for the success or failure of negotiations accompanied by the model of Third-Party intervention in mediating peaceful settlements during armed conflicts. Apart from the method of mediation through the contrast approach, it also analyzes the differences with other mechanisms of conflict resolution including arbitration and litigation. It looks closely at the two different Third-Party roles: with authority, and third-party roles without authority. The latter option gravitates more towards mediation functions. As the factor of culture will also often affect how early in a dispute’s history third parties become involved, the paper also identifies which Third Party roles are available to disputants, as well as the third party’s inclination to focus on interests and rights. Through the method of a case study of the peaceful negotiations for achieving the Ohrid Framework Agreement (which stopped the armed conflict of 2001 in North Macedonia) the paper explores the comparative functions of the intervention by the international envoys in the capacity of a Third Party.